QUALITATIVE STUDY OF DETERMINANTS OF PREGNANCY IN ADOLESCENTS IN CENTRAL MALUKU DISTRICT - Kiriwenno, Erlin; Sulistyowati, Sri; Saptaningtyas, Haryani; Anantanyu, Sapja (Mulawarman International Conference on Tropical Public Health, 2025)
Background :SOne of the health problems in Indonesia is teenage pregnancy, which is a pregnancy that occurs relatively easily under the age of 20. The younger the teenage girl is pregnant, the greater the risk of complications and death. This is because the reproductive organs in adolescents are not ready for pregnancy Objective : The purpose of this study was to analyze the determinants of pregnancy in adolescents in Central Maluku Regency Research Methods/ Implementation Methods : This research method uses a qualitative research method with a phenomenological approach. Data collection techniques in the study used In-depth interviews. The selection of informants was carried out by purposive sampling. The subjects of the study were adolescents experiencing pregnancy aged 15-19 years as many as 4 people and 2 health workers. Data were analyzed using the Miles and Huberman interactive model through the following stages: Data collection, data presentation, data reduction, and conclusions Results : Results Based on the results of the study of determinants of pregnancy in adolescents, it shows that 1) Low knowledge of adolescents about pregnancy, 2) Having premarital sex, 3) Lack of information and education (KIE) on adolescent reproductive health, 4) Lack of adolescent health care services (PKPR) and 5) The influence of socio-cultural factors that still marry off minors. Conclusion/Lesson Learned : Conclusion Thus, it can be concluded that determinants of pregnancy in adolescents can affect the high incidence of adolescent pregnancy in Central Maluku Regency. Therefore, there needs to be education and counseling about reproductive health that can prevent pregnancy in adolescents.